Evaluation of CD44 Variant Expression in Oral, Head and Neck Squamous Cell Carcinomas Using a Triple Approach and its Clinical Significance. (July 2014) - Athanassiou-Papaefthymiou, M.; Shkeir, O.; Kim, D.; Divi, V.; Matossian, M.; Owen, J.H.; Czerwinski, M.J.; Papagerakis, P.; McHugh, J.; Bradford, C.R.; Carey, T.E.; Wolf, G.T.; et al.
Cancer stem cells possess the qualities of self-renewal, tumorigenesis and the ability to recapitulate a heterogeneous tumor. Our group was the first to isolate head and neck squamous cell carcinoma (HNSCC) stem cells using the cell surface marker CD44. CD44 is a trans-membrane glycoprotein with a multitude of key-functions that regulate cancer cell proliferation and metastasis. The variety of CD44 functions is due to tissue-specific patterns of glycosylation of the extracellular portion, and to the multiple protein isoforms (CD44 variants, CD44v) generated by alternative splicing. This study investigates the expression pattern of CD44 variants in HNSCC. Ten cell lines from the most common HNSCC locations and representative of various clinical outcomes were assayed by quantitative real-time PCR, flow cytometry and immunofluorescence comparatively with normal oral keratinocytes. The CD44 v4 and v6 were exclusively abundant in HNSCC while the isoform v1, 2 was expressed in normal oral keratinocytes. Of interest, the highest level of CD44v6 expression was detected in advanced metastatic HNSCC, suggesting a link between CD44v6 expression and HNSCC metastasis, while the highest CD44v4 was detected in a stage IV HNSCC refractory to chemotherapy which developed recurrence. Oral-derived HNSCC expressed the highest CD44v4 and v6, and levels corresponded with staging, showing also an increasing tendency with recurrence and metastasis. CD44v were detected predominantly in smaller cells (a characteristic that has been associated with stem cell properties) or cells with mesenchymal morphology (a characteristic that has been associated with the migratory and invasive potential of epithelial tumor cells), suggesting that CD44v differential expression in HNSCC may be representative of the morphological changes inherent during tumor progression towards a more aggressive potential, and thus contributing to the individual tumor biology. The mechanism of CD44 variant involvement in HNSCC progression and metastasis is under investigation.